You need to convert the interest rate such that when compounded at a

frequency equal to the payments frequency, the result is the same as

the "quoted rate frequency"...quite a mouthful, I know!

EXAMPLE: on a monthly payment loan, if the rate is quoted as 12% compounded

semiannually, then a rate compounded monthly needs to be calculated in order to

make it "fit" the formula.

Using g as the quoted annual rate compounding semiannually and h as the "monthly" rate:

(1 + h/12)^12 = (1 + g/2)^2 ; do the math to get:

h = 12[(1 + g/2)^(1/6) - 1]

With g = 12% : h = 12[(1 + .12/2)^(1/6) - 1] = .1171055... (or 11.71%).

In other words, charging interest 12 times per year at 11.71% is the same

as charging interest 2 times per year at 12%.

With your formula, I suggest you replace (g-i) with k,

where k = h - i and h = as above.

Treat the initial investment (call it A) separately:

A(1 + k/12)^(fn)

Hope I was clear enough; not too easy to explain without chalkboard